Mindfulness, Age and Gender as Protective Factors Against Psychological Distress During COVID-19 Pandemic - Conversano, Ciro; Di Giuseppe, Mariagrazia; Miccoli, Mario; Ciacchini, Rebecca; Gemignani, Angelo; Orrù, Graziella (Frontiers in Psychology, 2020)
Objective: Mindfulness disposition is associated with various psychological factors and prevent emotional distress in chronic diseases. In the present study, we analyzed the key role of mindfulness dispositions in protecting the individual against psychological distress consequent to COVID-19 social distancing and quarantining. Methods: An online survey was launched on March 13, 2020, with 6,412 responses by April 6, 2020. Socio-demographic information, exposure to the pandemic, and quarantining were assessed together with psychological distress and mindfulness disposition. Multivariate linear regression analysis was performed to study the influence of predictive factors on psychological distress and quality of life in Italian responders during the early days of lockdown. Pearson correlations were calculated to study the relations between mindfulness and psychiatric symptoms. Results: Multivariate linear regression run on socio-demographics, COVID-19-related variables, and mindfulness disposition as moderators of overall psychological distress showed that mindfulness was the best predictor of psychological distress (β = -0.504; p = .000). High negative correlations were found between mindfulness disposition and overall Global Severity Index (r = -.637; p = .000), while moderate to high associations were found between mindfulness and all SCL-90 sub-scales. Discussion: Findings showed that high dispositional mindfulness enhances well-being and helps in dealing with stressful situations such as the COVID-19 pandemic. Mindfulness-based mental training could represent an effective intervention to stem the post-traumatic psychopathological beginnings and preventing the onset of chronic mental disorders.